(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Women health is the prime concern in Ayurveda classics, all gynecological problems are described under Yonivyapada and Aartav Vikara. Due to stressful lifestyle of today’s women, many physiological changes occur that ends with the disruption of HPO axis leading to various gynecological disorders. Eventually all these factors lead to infertility. A female patient aged 21 years having BMI 18 came to OPD of Rajiv Gandhi Govt. PG Ayurvedic Hospital, Paprola, with complaint of inability to conceive since last 3 years. She was taking treatment for the same from last one year by consulting some private practitioner All the routine investigations of both partners were within normal range. Semen analysis of her husband was normal. The causative factor behind unexplained infertility was elicited as Dhatukshya Janya Bandhyatva. Aim and Objectives: To study the efficacy of Balya and Brihmana Chikitsa in case of Dhatukshya Janya Bandhyatva. Methodology: Mustadi Yapna Basti and Shatavariyadi Ghrit Anuvasan Basti given in Kala Krama followed by Phalaghrita Uttar Basti in three consecutive cycles for Kshetra preparation along with oral medication. Discussion: Vata and Dhatu Kshaya are considered as main factors of Bandhyatva in this case. Thus, the treatment is directed towards pacifying the vitiated Vata Dosha. Here Yapna, Anuvasan and Uttar Basti lead to Dhatupushti by correcting the Jatharagni and Dhatvagni. Results: After this treatment patient conceived spontaneously. Conclusion: Dhatukshya a major factor which is often ignored while treating infertility patients should be paid prime concern when no other considerable etiological factor found during investigations.